PENGARUH SERVANT LEADERSHIP TERHADAP BUDAYA ORGANISASI, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN KINERJA KARYAWAN (STUDI PADA KARYAWAN PT. PRIMA ZIRANG UTAMA SEMARANG) - Widiartanto Widiartanto; Anis Qomariyah (Universitas Halu Oleo, 2022)
Entering the industrial revolution 4.0, the paradigm of competition that is material in nature shifts to the paradigm of competition that is knowledge development. Thus, the aspect of human resources plays a central role in achieving competitive advantage. Servant Leadership is a form of leadership that is considered the best form of leadership in order to create a competitive advantage based on human resources. This study aims to determine the effect of servant leadership on employee performance, the influence of servant leadership on organizational citizenship behavior, the influence of servant leadership on organizational culture, the influence of organizational culture on organizational citizenship behavior, and the influence of organizational citizenship behavior on employee performance. The approach used in this study is a quantitative approach with data collection techniques through surveys. The results show that there is a positive and significant influence between servant leadership on employee performance, a positive and significant influence between servant leadership on organizational citizenship behavior, a positive and significant influence between servant leadership on organizational culture, a positive and significant influence between organizational culture on organizational citizenship behavior, positive and significant influence between organizational culture on employee performance, positive and significant influence between organizational citizenship behavior on employee performance.